Rail mass transit for developing countries proceedings of the conference organised by the Institution of Civil Engineers and held in London on 9-10 October 1989. (Thomas Telford, 1990)
Many developing countries are building metro systems, which have encouraged economic growth in city centres but are proving enormously costly. This book forms a useful study of the arguments for and against metros, based on analyses of the advantages and problems encountered in several cities throughout the world.